2008
DOI: 10.1080/02786820802220274
|View full text |Cite
|
Sign up to set email alerts
|

Resuspension of Dust Particles in a Chamber and Associated Environmental Factors

Abstract: Experiments investigating particle resuspension from human activities were conducted in a full-scale experimental chamber. The experiments tested three types of flooring (vinyl tiles, new and old level-loop carpets) and two ventilation configurations (ceiling and side wall supply systems). The floorings were seeded with 0.1-10 µm test particles. The airborne particle concentration was measured by an array of optical particle counters (OPCs) in the chamber. Resuspension rates were estimated in size ranges of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 25 publications
13
158
0
1
Order By: Relevance
“…They showed the details of transient particle re-suspension and dispersion in the room and were able to predict overall re-suspension rates, but the removal of particulates from the carpet layer was idealized solely as a mass displacement effect. Predicted re-suspension rates ranged from 3.7 × 10 -5 to 8.1 × 10 -5 s -1 for two size classes of particles (2.7 and 7.7 µm), which is slightly greater than other experiments (Gomes et al 2007;Qian and Ferro 2008); however, the total particle number concentrations at several locations showed reasonably good agreement with experimental data (Rosati et al 2008).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…They showed the details of transient particle re-suspension and dispersion in the room and were able to predict overall re-suspension rates, but the removal of particulates from the carpet layer was idealized solely as a mass displacement effect. Predicted re-suspension rates ranged from 3.7 × 10 -5 to 8.1 × 10 -5 s -1 for two size classes of particles (2.7 and 7.7 µm), which is slightly greater than other experiments (Gomes et al 2007;Qian and Ferro 2008); however, the total particle number concentrations at several locations showed reasonably good agreement with experimental data (Rosati et al 2008).…”
Section: Introductionsupporting
confidence: 57%
“…The details are summarized in Table 3. Figure 16 shows a comparison of the predicted re-suspension rates for different particle sizes with those in experiments (Gomes et al 2007;Qian and Ferro 2008) and the numerical simulation (Oberoi et al 2010). Recent experiments showed that average re-suspension rates ranged from 10 -5 to 10 -2 h -1…”
Section: Particle Re-suspension Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments on resuspension caused by human indoor activities, such as walking and cleaning, have focused on particles B1 mm. In general, the resuspension rate increases with increasing particles size from 1 mm to over 10 mm (Qian and Ferro, 2008). Therefore, human activities may cause resuspension of manufactured nanoparticles attached to super-micron particles.…”
Section: Surface Contaminationmentioning
confidence: 99%